Determining the Presence of Lead in Various Brands of Commercial Hair Dyes by Atomic Absorption Spectroscopy - Anita (International Journal of Medical Toxicology and Legal Medicine, 2024)
Forensic analysis of hair dyes may offer higher-level information regarding oxidative and non-oxidative dyes. Prolonged exposure to heavy metals, such as arsenic, mercury, lead, nickel, cadmium, and copper, can pose a significant health risk. It is evident that heavy metals and their by-products present in cosmetic products such as lipsticks, soaps, face creams, hair gel, and hair dyes are absorbed in the bloodstream through the skin and root of the hair, and atomic absorption spectroscopy was used to investigate 10 hair dye samples from various manufacturers in the current study. This study focuses on evaluating the level of lead contamination in hair dyes that are frequently used by Indians. The results showed that the lead concentration was higher than the WHO/FDA-set maximum allowable level. Consequently, the continuous use of hair dyes can be prevented. Chronic or dangerous impacts are possible because of health hazards linked to exposure to contaminants through the skin or other pathways.